What keeps family physicians busy in Portugal? A multicentre observational study of work other than direct patient contacts. Issue 6 (15th June 2014) - Granja, Mónica; Ponte, Carla; Cavadas, Luís Filipe
Abstract : Objectives: To quantify the time spent by family physicians (FP) on tasks other than direct patient contact, to evaluate job satisfaction, to analyse the association between time spent on tasks and physician characteristics, the association between the number of tasks performed and physician characteristics and the association between time spent on tasks and job satisfaction. Design: Cross-sectional, using time-and-motion techniques. Two workdays were documented by direct observation. A significance level of 0.05 was adopted. Setting: Multicentric in 104 Portuguese family practices. Participants: A convenience sample of FP, with lists of over 1000 patients, teaching senior medical students and first-year family medicine residents in 2012, was obtained. Of the 217 FP invited to participate, 155 completed the study. Main outcomes measured: Time spent on tasks other than direct patient contact and on the performance of more than one task simultaneously, the number of direct patient contacts in the office, the number of indirect patient contacts, job satisfaction, demographic and professional characteristics associated with time spent on tasks and the number of different tasks performed, and the association between time spent on tasks and job satisfaction. Results: FP (n=155) spent a mean of 143.6 min/day (95% CI 135.2 to 152.0) performing tasks such as prescription refills, teaching, meetings, management and communication with other professionals (33.4% of their workload). FP with larger patient lists spent less time on these tasks (p=0.002). Older FP (p=0.021) and those with larger lists (p=0.011) performed fewer tasks. The mean job satisfaction score was 3.5 (out of 5). No association was found between job satisfaction and time spent on tasks. Conclusions: FP spent one-third of their workday in coordinating care, teaching and managing. Time devoted to these tasks decreases with increasing list size and physician age.